Feelings of pleasure, arousal, and dominance: men and women's responses to athletic images in different types of sports. Issue 7 (3rd October 2022) - Xu, Qingru; Billings, Andrew C.
ABSTRACT: This experiment aimed to examine emotional responses to athletic images featuring male and female athletes in 'gender-appropriate', 'gender-neutral', and 'gender-inappropriate' sports. Recruiting 236 subjects, this research has complex findings. The findings include – that when viewing pictures featuring male athletes, female subjects reported a significantly higher level of pleasure and arousal compared to their male counterparts; that regarding affective responses to different types of sports, male subjects reported the lowest level of pleasure and arousal in viewing athletes competing in 'gender-inappropriate' sports and that when viewing pictures featuring athletes competing in 'gender-inappropriate' sports, female subjects reported a significantly higher level of pleasure, arousal, and dominance than their male counterparts. Possible explanations and implications are discussed.